2013
DOI: 10.3130/aijs.78.1027
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Age and Cure on Fracture Properties of Concrete Subjected to High Temperature Heating

Abstract: This paper reports on the investigation into the influence of age and cure on fracture properties of concrete subjected to the effect of high temperature heating up to 800°C. Wedge splitting tests were conducted to measure the load versus crack mouth opening displacement curves. The initial cohesive stress and fracture energy were estimated by the inverse analysis of tension softening diagram calculated by the load versus crack mouth opening displacement curves. As a result, the effect of age and cure on the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…This may have been caused by microcracks: microcracks yielded during drying due to the difference of shrinkage strain between aggregate and cement paste should create multiple cracks under bending moment, and resultantly, it is considered to increase the total mechanical work. In addition, similar result about the fracture energy has been reported (Matsuzawa and Kitsutaka 2013). The shrinkage of the wall dummy and cylinder specimens during the drying period is shown in Fig.…”
Section: Loading Tests Of the Rc Wall Specimenssupporting
confidence: 84%
“…This may have been caused by microcracks: microcracks yielded during drying due to the difference of shrinkage strain between aggregate and cement paste should create multiple cracks under bending moment, and resultantly, it is considered to increase the total mechanical work. In addition, similar result about the fracture energy has been reported (Matsuzawa and Kitsutaka 2013). The shrinkage of the wall dummy and cylinder specimens during the drying period is shown in Fig.…”
Section: Loading Tests Of the Rc Wall Specimenssupporting
confidence: 84%
“…At present, many researchers have carried out an in-depth analysis and discussion on the fracture energy [12][13][14][15][16][17] of natural aggregate concrete (NAC) under ambient temperature, while the studies on the fracture energy is less after exposure to high temperature, and the conclusions obtained from these studies are even contradictory. For example, according to the investigations of Bažant 18 and Tang, 19 it has been found that the G F of NAC decreased with the increase of temperature before 500 C. In contrast, the experiments conducted by Baker, 20 Zhang, 21 Nielsen, 22 Menou, 23 Matsuzawa, 24 and Chen 25 resulted in the opposite, with the researchers concluding that the G F of the NAC increased before the temperature reaches 300 C and decreased with the incremental of temperature after 300 C. The main reason for this phenomenon may be that there are more micro cracks in the concrete after proper high temperature, which absorb more energy in the process of fracture, leading to the increase G F of NAC.…”
Section: Introductionmentioning
confidence: 98%